Successful Free Tissue Transfer in the Profoundly Hypercoagulable Glioblastoma Multiforme Patient: Surgical Experience and Anticoagulation Protocol - Niziol, Paul A.; Doval, Andres F.; Jalalabadi, Faryan; Klebuc, Michael (Journal of Reconstructive Microsurgery Open, 2020)
Background Glioblastoma multiforme (GBM) produces a hypercoagulable environment and is associated the highest rates of deep venous thrombosis (DVT) and pulmonary emboli (PE) of any malignancy. The use of postoperative radiation in this generally compromised patient group is associated with the development of complex scalp wounds. Free tissue transfer reconstruction will be essential in selected cases despite the presence of an underlying hypercoagulable state.Methods A 67-year-old female with a history of previous DVT presented with osteoradionecrosis and infected scalp wound following GBM treatment. She underwent reconstruction with a free vastus lateralis flap and skin graft. Initial anticoagulation was provided with intravenous heparin and transitioned to oral apixaban. Wound cultures demonstrated coagulase-negative Staphylococcus, Actinomyces neuii, and Peptoniphilus harei and were treated with a 6-week course of intravenous cefepime and vancomycin.Results Despite the initial failure of a local scalp rotation flap, successful wound healing was achieved with a free muscle flap and a course of culture specific antibiotics. The patient succumbed to recurrent disease 22 months after surgery, underscoring the importance of limiting hospitalization and maximizing quality of life in this group of patients.Conclusion Free tissue transfer can be successfully achieved in the hypercoagulable GBM patient. Heparin and apixaban were employed successfully in the prevention of thrombotic events. Antiplatelet therapy should also be considered to counteract platelet aggregation induced by the transmembrane glycoprotein (podoplanin) that is expressed on GBM tumor cells. Enzyme-linked immunosorbent assay testing (ELISA) of blood soluble podoplanin may help determine the degree of hypercoagulability and guide therapy.
Keywords: glioblastoma; free tissue flaps; thrombophilia